2007
DOI: 10.3354/ame01132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B-vitamins (B1, B12) and inorganic nutrients on algal bloom dynamics in a coastal ecosystem

Abstract: Vitamins play an integral role in the cellular biochemistry of algae, but the effect of these organic metabolites on the growth and diversity of phytoplankton communities has been poorly studied. We integrated newly developed techniques to directly measure vitamins B 1 and B 12 with field-based amendment experiments to elucidate the role of B-vitamins in phytoplankton population dynamics in coastal marine environments. Two sites on Long Island, New York, USA, were monitored from spring through fall: the tidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
155
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 34 publications
7
155
0
2
Order By: Relevance
“…Our quantitative results demonstrate that vitamins B 1 and B 12 can limit the accumulation of microalgal biomass over a wide range of concentrations, and that the limiting concentrations for some species in culture are higher than levels present in some coastal waters. For example, the growth of the toxic dinoflagellate Karenia mikimotoi and the "brown tide" species Aureococcus anophagefferens displayed half-saturation constants of 13.1 and 3.49 pM, respectively, for vitamin B 12 (Table 2), which are similar to concentrations typically found in coastal systems (0.5-20 pM) (18,22). In the case of A. anophagefferens, the genomic presence of a vitamin B 12 -dependent methionine synthase (metH) and absence of the vitamin B 12 -independent methionine synthase (metE) confirms its absolute requirement of this vitamin (15).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our quantitative results demonstrate that vitamins B 1 and B 12 can limit the accumulation of microalgal biomass over a wide range of concentrations, and that the limiting concentrations for some species in culture are higher than levels present in some coastal waters. For example, the growth of the toxic dinoflagellate Karenia mikimotoi and the "brown tide" species Aureococcus anophagefferens displayed half-saturation constants of 13.1 and 3.49 pM, respectively, for vitamin B 12 (Table 2), which are similar to concentrations typically found in coastal systems (0.5-20 pM) (18,22). In the case of A. anophagefferens, the genomic presence of a vitamin B 12 -dependent methionine synthase (metH) and absence of the vitamin B 12 -independent methionine synthase (metE) confirms its absolute requirement of this vitamin (15).…”
Section: Discussionsupporting
confidence: 56%
“…Studies measuring vitamin B 12 in the ocean have shown levels are lower than those estimated by prior bioassays (18) and in many cases, concentrations of levels are substantially less than the 7-pM threshold (18) putatively required by many phytoplankton in culture (15). A series of studies have demonstrated that vitamins can stimulate phytoplankton growth in Fe-limited, high-nutrient, low-chlorophyll (HNLC) regions of Antarctica (19,20) and coastal zones where HABs commonly occur (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if there is a reliable and abundant external source of B 12 , and these conditions prevail over a long period of time, the gene may be lost entirely, which is the derived state of many algal species spanning multiple diverse phyla (Croft et al, 2005;Helliwell et al, 2011). However, natural levels of B 12 are reportedly less than 10 ng L 21 (10 pM) in freshwater (Kurata, 1986) and perhaps up to 70 ng L 21 in seawater (Carlucci, 1970;Gobler et al, 2007), with more recent measurements indicating a lower range in the photic zone of the Southern Ocean and North Atlantic Ocean (Panzeca et al, 2009;Sañudo-Wilhelmy et al, 2012). The extracellular concentration of B 12 necessary to repress the METE transcript (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Improved methodology for the quantification of thiamine and cobalamin in environmental samples revealed a heterogenous distribution of these vitamins in the oceans, with generally very low levels free in solution in the photic zone (Sañudo-Wilhelmy et al, 2012). It has also been shown, through fertilization experiments, that vitamins are limiting for algal growth in several marine environments (Gobler et al, 2007). Therefore, it is intriguing that many oligotrophic species such as Ostreococcus tauri are nonetheless vitamin auxotrophs (Worden et al, 2009;Helliwell et al, 2011) and so must be able to obtain a ready source of these organic micronutrients from their surroundings.…”
mentioning
confidence: 99%